1998
DOI: 10.1038/bjc.1998.559
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of 5-aminolaevulinic acid-induced protoporphyrin IX accumulation: a study in patients with (pre)malignant lesions of the oesophagus

Abstract: Summary Administration of 5-aminolaevulinic acid (ALA) leads to porphyrin accumulation in malignant and premalignant tissues, and ALA is used as a prodrug in photodynamic therapy (PDT). To understand the mechanism of porphyrin accumulation after the administration of ALA and to investigate whether ALA-induced protoporphyrin IX Correspondence to: FWM de Rooij lead to the development of adenocarcinoma through a multistep process of progression from metaplasia to lo%--agrade dysplasia.high-grade dysplasia and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 22 publications
2
71
1
2
Order By: Relevance
“…The grade of tumour differentiation and the grade of dysplasia in Barrett's mucosa were described according to Haggitt (Haggitt, 1994). In addition, adjacent biopsies were kept at -70°C until the activities of PBG-D and FC and porphyrin concentrations were determined (Hinnen et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grade of tumour differentiation and the grade of dysplasia in Barrett's mucosa were described according to Haggitt (Haggitt, 1994). In addition, adjacent biopsies were kept at -70°C until the activities of PBG-D and FC and porphyrin concentrations were determined (Hinnen et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…As a result porphyrins, predominantly PPIX, will accumulate (Bishop and Desnick, 1982;Kennedy and Pottier, 1992). Previously, we observed an imbalance between the activities of PBG-D and FC in BE and AC (Hinnen et al, 1998). The ratio between PBG-D and FC activities, normalized for squamous epithelium, was found to be significantly higher in BE and AC.…”
mentioning
confidence: 99%
“…The power of elevated activity of PBGD to produce PpIX was clinically demonstrated for malignant gliomas (Stummer et al, 1998b); oral cavity cancer (Leunig et al, 2000a); colonic and gastrointestinal dysplasia (Stepp et al, 1998); peritoneal endometriosis (Hillemanns et al, 2000); laryngeal neoplasms (Leunig et al, 2000b); malignant lesions of the oesophagus (Hinnen et al, 1998); lower urinary tract tumours (Kriegmair et al, 1999); bladder cancer (Kriegmair et al, 1996); malignant mucosa in head and neck cancer (Betz et al, 1999); Barrett's oesophagus and adenocarcinoma (Stepp et al, 1998); basal and squamous cell carcinoma (Orenstein et al, 1995(Orenstein et al, , 1996(Orenstein et al, , 1997Malik et al, 1998) and coetaneous lymphoma (Orenstein et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it was demonstrated that malignant gliomas (Stummer et al, 1998), colonic and gastrointestinal dysplasia , malignant lesions of the esophagus (Hinnen et al, 1998), bladder cancer (Kriegmair et al, 1996), basal and squamous carcinoma (Orenstein et al, 1995(Orenstein et al, , 1996Malik et al, 1998) and cutaneous lymphoma (Orenstein et al, 2000) produce excess PpIX following 5-ALA administration. One possible rationale for the specificity of PpIX accumulation through increased PBGD activity in rapidly dividing cancer cells is that their enhanced metabolism demands additional heme, which is mandatory for an increased aerobic ATP supply connected to the energy demands of the tumor.…”
Section: Introductionmentioning
confidence: 99%